PENGARUH LATIHAN SLED TOWING OR SPEED CORD TOWING TERHADAP KECEPATAN PEMAIN SEPAKBOLA SMA NEGERI 1 PEKANBARU - farizwan, Muhammad farizwan; Juita, Ardiah Juita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The issues raised in this research is “Are there exercises influence sled cord towing or towing speed to the speed of the high school football players STATE 1 pekanbaru?”.This research is aimed eksperrimen study to determine the effect of exercise sled cord towing towing speed or the speed at high school football players STATE 1 pekanbaru.Populasi is used throughout the class 1 high school football players STATE 1 pekanbaru.This study used purposive sampling technique is sampling wiyh certain considerations,which specializes in group SMA Negeri 1 Pekanbaru.Data were obtained and collected through the initial test and final test before and after exercise or speed sled towing towing cord using speed measuring devices that run the spirit of 100 yard.Metode data processing using statiscial calculations and to test the hypothesis using the t test,the hypothesis that used in this study was the effect of exercise sled towing towing cord or speed to the speed of the high school football players STATE 1 pekanbaru.t test research result yield of 5,95 and ttable 1,761 at significant level of 0,05.means > t table. It can be concluded that ha accepted,it concludes that there is a significant effect of exercise sled towing towing cord or speed to the speed of the high school football players STATE 1 pekanbaru. Key Words: Sled towing or speed cord towing Speed